Dominance of electroactive microbiomes in bioelectrochemical remediation of hydrocarbon-contaminated soils with different textures. (November 2019) - Wang, Huan; Lu, Lu; Mao, Deqiang; Huang, Zhe; Cui, Yixiao; Jin, Song; Zuo, Yi; Ren, Zhiyong Jason
Abstract: Bioelectrochemical systems (BESs) are known to enhance the remediation of hydrocarbon-contaminated soil and sediments compared with natural attenuation, and the primary mechanism has been assumed as anaerobic degradation facilitated by electroactive bacteria (EAB) using the electrode as electron acceptor. However, known EAB were rarely found on the anodes of reported BESs, which challenged the fundamental mechanism of BESs although significant current generation was always observed during degradation of these recalcitrant substrates. This study however found the abundant EAB Geobacter (∼27.3%) in the anodic biofilms, which confirmed the role of electroactive bio-anode on the conversion of hydrocarbons into the current for the enhancement of remediation. Widespread occurrence of aerobic hydrocarbon-degrading bacteria (HDB) (e.g. ∼24.0% Parvibaculum and ∼30.6% Pseudomonas ) was observed in soils with limited dissolved oxygen (∼0.4 mg/L). The higher abundance of dehydrogenase genes was found in the anode biofilms than that in soils, indicating anodic microorganisms may be mainly responsible for the removal of intermediates of aerobic hydrocarbons degradation in soils. High water saturation level and sandy soil texture showed positive impacts on bioelectrochemical remediation, while clay soil and unsaturation condition pose challenges in mass transfers in the matrix. The reactor performance was consistent with the phylogenetic molecular ecological network (pMENs) analysis, which showed that sandy soil BESs had tighter microbial network interactions than clay soil reactors. Graphical abstract: Image 1 Highlights: High abundance of Geobacter was found in the anodic communities of soil BESs. Widespread occurrence of aerobic hydrocarbon-degrading bacteria in anoxic soils. High water content and sandy soil texture positively impact remediation. Tighter ecological network interaction means high remediation efficiency.